Caracterização sensorial de vinhos finos do bioma caatinga - Veríssimo, Caio Monteiro (2020)
The São Francisco Valley, located between the 8° S and 9° S parallels, in the northeast of Brazil, is characterized by a semi-arid tropical climate, with high insolation rate and low rainfall, which together with irrigation management and pruning, make it possible to produce grapes and wines throughout the year. Such unique characteristics of Terroir enable a product with a particular chemical and sensory profile, such as high levels of phenolic compounds, intense coloring and marked fruity notes. Thus, the objective of this study was to sensorially characterize commercial samples of tropical red wines (Vitis vinifera L.) from the São Francisco Valley through different descriptive methods, comparing them according to its power of description and discrimination, as well as their similarities. In addition, the physicochemical profile of samples was evaluated, investigating how these variables interfere in the sensory perception of consumers who received a short sensory training. For this, nine wine samples produced with different cultivars, between young and aged in French oak barrels, were evaluated for their sensory attributes using Descriptive Analysis (DA) with trained assessors (n=8) and the Check- all-that-apply (CATA) with consumers (n=100) and with consumers who received a short training (n=30). The physicochemical characterization was based on classic enological, spectrophotometric and colorimetric parameters. Assessing the sensory profile obtained by the three methods, young wines were more impacted by characteristics such as red-violet color, fruity aromas, greater vivacity and medium body. Aged wines were characterized by intense ruby color, notes of fruit jam, greater body and high aromatic and gustative intensity. However, the identification, both by the trained staff, as well as by consumers, of attributes related to sensory defects, such as alcoholic notes, acidity and bitterness can generate a negative repercussion of the products in the wine consumer market. Regarding the comparison of methods, DA and CATA with semi-trained panellists provided, in addition to a greater capacity of description and discrimination of samples, a higher similarity index for aged samples (95%). An improvement of 30% in the descriptive power of the samples, as well as an increase on attribute citation frequency was achieved by implementing a quick sensory training to consumers, also allowing for a reduction of 70% in the size of the panel. As expected, a lower understanding related to fewer usual terms was observed in both CATA variations. For the physicochemical profile, the wines presented parameters consistent with those governed by Brazilian legislation, in addition to high levels of total polyphenols and total anthocyanins. The chromatic composition, however, indicated an undesired color evolution for young samples. Regarding the perception by consumers who receive a quick sensory training, it was possible to identify that physicochemical attributes, in isolation, may not impact in the perception of analogous sensory characteristics, such as acidity and astringency. Through this study, it can be concluded that the evaluated tropical wines reflect the Terroir of the region, not only by sensory characteristics, but also by the chemical composition, which can provide beneficial health effects, preventing cardiovascular and chronic-degenerative diseases.